"A bulletin board of dreams": corporate empowerment promotion and feminist implications. Issue 4 (1st October 2016) - Tornhill, Sofie
ABSTRACT: This article examines the premises of corporate solutions to gender inequality in the Global South. In feminist debates, businesses' increasing emphasis on women's empowerment has been discussed both in terms of increasing feminist impact and the co-optation of feminist demands. To explore the ideological effects of corporate gender practices, focus is placed on the Coca-Cola Company's global "5by20" campaign, which has the stated aim to empower five million women as small-scale entrepreneurs around the world and, in a "win–win" fashion, to double sales by 2020. Based on interviews and participatory observations in Mexico, this article traces a particular narrative of empowerment, envisioned as a transition from dependency to self-sufficiency and threatened by psychological and cultural restraints rather than material conditions. It shows that self-help and positive thinking are essential affective drives, thus reinforcing market-based, individualized development strategies. In response to feminist debates, the article concludes that corporate gender practices can be seen as part of a neoliberal transposition of equality concerns from a political to an economic domain. In effect, when initiatives such as 5by20 promote the accumulation of "human capital" to enhance gender equality, they simultaneously work to legitimize the inequalities that are necessarily entailed in competitive capitalism.